Regularities of defect development in the asphalt concrete road pavements - Sivilevičius, Henrikas; Petkevičius, Kazys (Journal of Civil Engineering and Management, 2002)
A new classification of asphalt concerete pavement defects is presented in the article and the causes of their development are systematised. The dynamics of asphalt concrete pavement defect development in the road and the dependence of pavement deterioration on the type of defects are presented in the theoretical graphic model. The change of road pavement structural strength (stiffness modulus) depending on the pavement service life is also described. The dependence of the level of asphalt concrete pavement on the most important roads of the Republic of Lithuania (road Vilnius-Kaunas [Al] and motorway Vilnius Panevėžys [A2]) measured with one-wheel dynamometric trailer PKRS-2U (Russia) on the level of pavement deterioration has been identified through experiments. The analysis of the dependence of transport costs and driving speed on road pavement level has been carried out. Regression equations of such dependence and correlation coefficients as well as relations are presented too.Frist Published Online: 30 Jul 2012